Effects of dietary arachidonic acid on reproduction performance, tissue fatty acid profile and gonadal steroidogenesis in female yellow catfish Pelteobagrus fulvidraco. (27th December 2020) - Fei, Shuzhan; Chen, Zheng; Xia, Yu; Liu, Haokun; Han, Dong; Jin, Junyan; Yang, Yunxia; Zhu, Xiaoming; Xie, Shouqi
Abstract: An 8‐week feeding experiment was performed to evaluate the effects of dietary arachidonic acid (ARA) on the reproductive performance, tissue fatty acid profile and sex hormone secretion in female Pelteobagrus fulvidraco during the breeding season. Three diets with different ARA levels (0.64%, 4.67% and 10.07% of total fatty acids) were formulated, a control diet (C) and two diets with low ARA (ARA‐L) or high ARA (ARA‐H). The results showed that the highest gonadosomatic index (GSI) and condition factor (CF) were observed in the ARA‐H group. The diets with supplementation of ARA resulted in a significantly higher fertilization rate, more normal larvae and greater survival rate of 7 days posthatching (7DPH) larvae. The ARA contents in liver and 3DPH larvae were improved with increasing dietary ARA concentrations. The lowest EPA/ARA ratios were observed in liver and eggs of fish fed with the ARA‐L diet. Significantly reduced serum estradiol (E2), 11‐keto‐testosterone (11‐KT) and testosterone (T) levels were found in the ARA‐L group females compared with the other treatments. The combined results indicated that a higher dietary ARA level and ARA/EPA ratio mainly influence spawning performance and egg quality of yellow catfish and that ARA regulates sex steroid hormone synthesis in broodstock.